The role of physical education teacher in shaping people's attitudes with disabilities towards physical activity - Dominika Wysokińska (Rozprawy Społeczne)
Abstract The study aimed to present retrospective assessment of the role of physical education teacher by adults with different levels of fitness in their current level of physical activity.